Dead mall (2022) ebook - Cesare, Adam (Dead Mall., 2023)
The Penn Mills Galleria is about to be demolished. Five teens sneak into the mall to take a last look around before it's gone.However, while Penn Mills has been closed for years, the mall is far from abandoned.A night of exploration becomes a shopping spree from hell. The teens must contend with the sprawling, transformative cosmic horror of Penn Mills or be trapped forever within the Dead Mall.A coming-of-age horror story that both engages and criticizes nostalgia culture while showing deep empathy for the fears and vulnerabilities of Gen-Z teenagers.A young adult graphic novel by Adam Cesare, author of Clown in a Cornfield, winner of the 2020 Bram Stoker Award for Superior Achievement in a Young Adult Novel.